The effect of preparation method and Sb content on SnO2-CuO sintering - Mazali, I. O.; Las, W. C.; Cilense, M. (Kluwer Academic Publ, 2003)
The sintering behavior of SnO2-CuO system has been investigated for two preparation methods and as a function of antimony concentration. A chemical preparation (Pechini's method) resulted in powders with smaller particle sizes than for a conventional oxide mixture. This led to smaller grain sizes in Pechini's method ceramics. The microstructures were heterogeneous in both systems, showing grain coarsening. The densification was aided by liquid phase formation, due to copper, in both systems, but the temperature of maximum shrinkage rate was larger for the Pechini's method ceramic because copper had to diffuse to the grain surface. Independently of the preparation method, antimony did not aid densification, and increasing its concentration led to a higher densification temperature and lower shrinkage rate. (C) 2003 Kluwer Academic Publishers.